Effects of resinous monomers used in restorative dental modeling on the cohesive strength of composite resin - Barcellos, Daphne Camara; Pucci, Cesar Rogerio [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Goto, Edson Hidenobu [UNESP]; Inocencio, Aline Cassia [UNESP] (My University, 2008)
Purpose: The purpose of this study was to evaluate the cohesive strength of the composite using different resinous monomers to lubricate instruments used in the Restorative Dental Modeling Insertion Technique (RDMIT). Materials and Methods: The composite specimens were made by using a prefabricated Teflon device. Different resinous monomers were used at the interface to lubricate the instruments, for a total of 72 specimens divided into 6 groups: 1. control group, no resinous monomer was used; 2. Composite Wetting Resin; 3. C & B Liquid; 4. Scotchbond Multi-Purpose Adhesive; 4. Adper Single Bond Adhesive; 6. Prime & Bond NT. Specimens were submitted to the circular area tensile test to evaluate the cohesive strength at the composite interfaces. Data were analyzed using ANOVA and Tukey's test (α = 0.05). Results: ANOVA showed a value of p < 0.0001, which indicated that there were significant differences among the groups. The means (SD) for the different groups were: Adper Single Bond Adhesive: 26 (12) a; control group: 28 (3) ab; Prime & Bond NT: 32 (12) ab; Composite Wetting Resin: 36 (9) abc; C&B Liquid: 38 (7) be; Scotchbond Multi-Purpose Adhesive: 46 (10) c. Groups denoted with the same letters were not significantly different. Only Scotchbond Multi-Purpose Adhesive, used for direct restorations, had a statistically significantly higher bond strength than the control group, Adper Single Bond Adhesive, and Prime & Bond NT. Adper Single Bond with Adhesive showed a statistically significantly lower mean value than C&B Liquid. Conclusion: The results of this study indicate that the resinous monomers used for lubricating the instruments in the RDMIT did not alter the mechanical properties of the composite, and therefore did not reduce the cohesive bond strength at the composite interfaces.
Keywords: Cohesive strength; Composite resin; Resinous monomer